Study the Effect of Adding Aluminum Nanoparticles to a Smart Alloy (Cu-Al-Ni) on Hardness and Porosity (Journal of Engineering, 2023)
This work deals with the effect of adding aluminum nanoparticles on the mechanical properties, micro-hardness and porosity of memory-shape alloys (Cu-Al-Ni). These alloys have wide applications in various industrial fields such as (high damping compounds and self-lubricating applications). The samples are manufactured using the powder metallurgy method, which involved pressing in only one direction and sintered in a furnace surrounded by an inert gas. Four percentages (0%, 5%, 10%, and 15%) of aluminum nanoparticles were fabricated, which depended on the weight of aluminum powder (13%) in the sample under study. To find out which phase is responsible for the reliability of the formation of this type of alloy and its porosity, X-ray diffraction (XRD) and scanning electron microscopy (SEM) tests are used. The Vickers micro-hardness and porosity properties of these alloys were studied using a Vickers micro-hardness and porosity tester according to ASTM b328-1996. The results showed that increasing the concentration of aluminum nanoparticles in the alloy led to an increase in hardness with a decrease in the porosity, and the sample (15%) gave the best hardness (190.8 HV). The sample (0%) gave the highest porosity (19.573) %.